Protective effect of notoginsenoside and tanshinone IIA on inflammation-related colorectal cancer mice and the inhibition effect on COX-2 expression - Cao Wen; Zhou Xiaoqing (KeAi Communications Co., Ltd., 2021)
Objective: To explore the preventive effects and possible me-chanisms of action of notoginsenoside (NGS) and tanshinone IIA (TSN) in inflammation-related colorectal cancer (IRCC) in mice. Methods: Eighty-eight male C57BL/6 mice were randomly assigned to 11 groups (n = 8 each group). Azomethane oxide + dextran sulfate (AOM + DSS) model control (model), NGS low-dose (l-NGS), NGS medium-dose (m-NGS), NGS high-dose (h-NGS), TSN low-dose (l-TSN), TSN medium-dose (m-TSN), TSN high-dose (h-TSN), (NGS + TSN) low-dose [l-(NGS + TSN)], (NGS + TSN) medium-dose [m-(NGS + TSN)], (NGS+TSN) high-dose [h-(NGS + TSN)], and blank groups were established. The first 10 groups were intraperitoneally injected with AOM to induce inflammatory colon cancer, whereas the blank group was intraperitoneally injected with 0.9% NaCl solution. The first 10 groups drank a 2.5% sodium DSS aqueous solution continuously from day 5 for three cycles (one cycle: five days, every three weeks), and the blank group was allowed free access to water. Drug groups were administered NGS (low, medium, or high dose), TSN (low, medium, or high dose), or NGS + TSN (low, medium, or high dose), and the model and blank groups were administered saline by lavage until the end of the experiment. The general activity, body weight, and survival rate of and incidence of adenocarcinoma in mice were detected and the expression of cyclooxygenase 2 (COX-2) was detected by immunohistochemistry. Results: (1) The survival rate of mice with IRCC in the h-NGS, m-TSN, h-TSN, m-(NGS + TSN), and h-(NGS + TSN) groups was significantly increased than that in other groups (P < 0.05). (2) The incidence of tumors in the h-(NGS + TSN), m-TSN, and l-NGS groups was significantly lower than that in the model group (P < 0.05). (3) The expression level of COX-2 in tumor tissues of mice in the m-(NGS + TSN) and h-(NGS + TSN) groups was significantly lower than that in the model group (P < 0.05). Conclusion: Tumor formation was inhibited by m-TSN and h-(NGS + TSN) treatments in mice with IRCC, and h-(NGS + TSN) treatment inhibited the COX-2 pathway.